Stock Dividend Announcement Effect: Evidence from the Stock Exchange of Thailand - จิโน, ปัญจพัฒน์; ทองคง, สุภา (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
The purpose of this research was to study stock dividend announcement effect to stock price of SET100 companies listed on The Stock Exchange of Thailand during the period 2014 to 2018. The sample consisted of 35 observations. Event Study Methodology (ESM) was applied to examine the market reaction to dividend announcement on the stock price surrounding forty-one days of announcement. The market model was used to generate the expected returns. Furthermore, the one sample t-test was employed to examine the significance of abnormal returns and cumulative abnormal returns. The findings from the stock dividend release sample indicated that there was a significant positive abnormal returns on the announcement dates. The cumulative abnormal returns existed 2.19% at a significant level of .05 besides, it found that there was an overreaction straight after the announcement day, then a correcting attempt in the post event and then it goes back to normal. It implies that stock prices do not drop shortly after the dividend announcement, which would specify that The Stock Exchange of Thailand is not exhibit semi-strong market efficiency according to Efficient Market Hypothesis (EMH).